2014
DOI: 10.1136/bmj.g4554
|View full text |Cite
|
Sign up to set email alerts
|

Population red blood cell folate concentrations for prevention of neural tube defects: bayesian model

Abstract: Objective To determine an optimal population red blood cell (RBC) folate concentration for the prevention of neural tube birth defects. Design Bayesian model. Setting Data from two population based studies in China.Participants 247 831 participants in a prospective community intervention project in China (1993-95) to prevent neural tube defects with 400 μg/day folic acid supplementation and 1194 participants in a population based randomized trial to evaluate the effect of folic acid supplementation on blood f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
219
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(230 citation statements)
references
References 45 publications
4
219
1
6
Order By: Relevance
“…Dotted lines represent the 95% credible interval. The shaded area (natural food intakes between 450 μg DFE/day and 650 g DFE/day) refer to the range of intakes and RBC folate concentrations associated with the lowest population risk for a NTD according to Crider et al (2014). Based on data from Marchetta et al (2015).…”
Section: Response Of Folate Status To Folate Intake and Supplementationmentioning
confidence: 99%
“…Dotted lines represent the 95% credible interval. The shaded area (natural food intakes between 450 μg DFE/day and 650 g DFE/day) refer to the range of intakes and RBC folate concentrations associated with the lowest population risk for a NTD according to Crider et al (2014). Based on data from Marchetta et al (2015).…”
Section: Response Of Folate Status To Folate Intake and Supplementationmentioning
confidence: 99%
“…European guidelines regarding FA supplementation do not currently feature an explicit recommendation concerning the required duration of FA supplementation preconceptionally. This suggests that there is a need to update our national and European FA guidelines to include a recommendation on the ideal timing of FA preconceptionally, in view of the recent kinetic studies in this area (7)(8)(9)(10) . This message should be incorporated into renewed public health campaigns in this area to enhance the clinical effectiveness of periconceptional FA supplementation.…”
Section: Public Health Nutritionmentioning
confidence: 99%
“…Given the limited Irish data describing the duration of periconceptional FA supplementation and the rising incidence of NTD in Ireland, examination of the duration of periconceptional FA supplementation is important. Kinetic studies have shown that those who consumed 400 µg FA/d reached an RBC folate concentration associated with optimally reduced risk of NTD after 3 to 6 months (7)(8)(9) . Therefore, it is important to establish whether or not women who take FA preconceptionally are doing so for the required duration to optimise NTD prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent kinetic studies, it has been shown that it takes 12 weeks of daily supplementation with 400μg FA to achieve the level of red cell folate (RCF) associated with reduced risk of neural tube defects (NTDs) (3) . The aim of this cross-sectional observational study was to analyse in detail the use of FA supplementation including timing of commencement and duration of usage; in women presenting for antenatal care in the first trimester of pregnancy.…”
mentioning
confidence: 99%